2012
DOI: 10.1523/jneurosci.5777-11.2012
|View full text |Cite
|
Sign up to set email alerts
|

Logarithmic Compression of Sensory Signals within the Dendritic Tree of a Collision-Sensitive Neuron

Abstract: Neurons in a variety of species, both vertebrate and invertebrate, encode the kinematics of objects approaching on a collision course through a time-varying firing rate profile that initially increases, then peaks, and eventually decays as collision becomes imminent. In this temporal profile, the peak firing rate signals when the approaching object's subtended size reaches an angular threshold, an event which has been related to the timing of escape behaviors. In a locust neuron called the lobula giant motion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 52 publications
3
33
0
Order By: Relevance
“…The most compelling studies on this subject have been carried out in the LGMD neuron of the locust, using biophysical computational models (Rind and Bramwell, 1996;Peron and Gabbiani, 2009;Jones and Gabbiani, 2012). In the present study, we showed that MLG2 shares several physiological features with the locust's LGMD and with the crab's MLG1.…”
Section: Physiological Model Of the Mlg2 Response To Looming Stimulisupporting
confidence: 57%
See 2 more Smart Citations
“…The most compelling studies on this subject have been carried out in the LGMD neuron of the locust, using biophysical computational models (Rind and Bramwell, 1996;Peron and Gabbiani, 2009;Jones and Gabbiani, 2012). In the present study, we showed that MLG2 shares several physiological features with the locust's LGMD and with the crab's MLG1.…”
Section: Physiological Model Of the Mlg2 Response To Looming Stimulisupporting
confidence: 57%
“…The model proposed by Jones and Gabbiani (2012) for the biophysical implementation of the computation performed by the locust's LGMD neuron in response to looming stimuli includes two aspects: (1) the effect of synaptic excitation and inhibition at the level of the LGMD's membrane potential (see below) and (2) the transformation of the membrane potential into the LGMD's firing rate by a nonlinear input-output relationship. To evaluate the relationship between the MLG2 membrane potential and its firing rate we employed a median filter to cut off the action potentials (Fig.…”
Section: Synaptic Inhibitionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, the interaction between retinotopic synaptic inputs and active dendritic conductances could increase responses to looming stimuli and opposed to matched, spatially randomized controls, thus implementing a form of visual object segmentation (R. Dewell and F. Gabbiani, unpublished observations). Testing this hypothesis will require us to incorporate the wiring scheme and active conductances in detailed compartmental simulations of the LGMD neuron along the lines of our previous simulations (Jones and Gabbiani 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Because the firing rate of the LGMD is described by multiplying the angular speed of an approaching object with a negative exponential of its angular size, this suggested that feed-forward inhibition might code for angular size [20]. Excitation has already been shown to encode a function of angular speed [27]. The electrophysiological recordings we report allowed us to test whether the firing rate of inhibitory neurons presynaptic to the LGMD encodes the angular size, or speed of looming stimuli, or functions of them.…”
Section: Introductionmentioning
confidence: 99%